Pengaruh Teknologi Informasi, Explicit Knowledge, Tacit Knowledge Terhadap Kinerja Karyawan - Febri Romadhan (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
The aim of this study is to investigate the impact of Information Technology, explicit knowledge and tacit knowledge, on employee performance in Citraland Gama City Field. The study uses a quantitative approach to evaluate employee performances in CitraLand Gama city Field. Samples are taken randomly, and data is collected using research instruments. Data is analyzed quantitatively using a double linear regression method. The data support is a questionnaire using a 5-point likert scale (where 5 refers to the highest level of agreement and 1 indicates the higher level of disagreement) used in this study. The variables studied include information technology, explicit knowledge, tacit knowledge and employee performance. Primary data is obtained from respondents through questionnaires. Data collected involves a closed questionnaire in which the answers provided by researchers are selected by respondents, with a total of respondents 50 employees. The dissemination of the questionnaire is done online via the Microsoft form.